Pengaruh Budaya Kerja, Disiplin Kerja Dan Semangat Kerja Terhadap Prestasi Kerja Anggota Sat Lantas Polres Kabupaten Empat Lawang - Teri Intaraga; Gayatri, Ida Ayu Made Ermeytha; Abi, Yudi Irawan (Jurnal Bisnis, Manajemen dan Akuntansi, 2025)
The purpose of this study was to determine the influence of work culture on the work performance of Traffic Unit Members of Empat Lawang District Police. To determine the influence of work discipline on the work performance of Traffic Unit Members of Empat Lawang District Police. To determine the influence of work spirit on the work performance of Traffic Unit Members of Empat Lawang District Police. To determine the influence of work culture, work discipline and work spirit on the work performance of Traffic Unit Members of Empat Lawang District Police. The sample in this study was 43 Traffic Unit Members of Empat Lawang District Police. So the sampling technique used in this study was the saturated sampling method. Saturated sampling can also mean the method used to determine the research sample is to take the entire population based on certain characteristics or traits as the subject of the research. The calculation results obtained a regression equation, namely: Y = 15,048 + 0.515 (X1) + 0.367 (X2) + 0.239 (X3). This means that if the variables of work culture (X1), work discipline (X2) and work spirit (X3) are increased, they will increase work performance (Y). Testing the influence of Work Culture (X1) on Work Performance (Y), obtained a significant value of 0.000 <0.05, this means that Work Culture (X1) has a significant effect on the variable Work Performance (Y). Testing the influence of Work Discipline (X2) on Work Performance (Y), obtained a significant value of 0.004 <0.05, this means that Work Discipline (X2) has a significant effect on the variable Work Performance (Y). Testing the influence of Work Spirit (X3) on Work Performance (Y), obtained a significant value of 0.031 <0.05, this means that Work Spirit (X3) has a significant effect on the variable Work Performance (Y). The results of simultaneous calculations obtained a significant value, 0.000 <0.05, this means that the variables Work Culture (X1), Work Discipline (X2) and Work Spirit (X3) have a significant effect together on Work Performance (Y).